Game change : Obama and the Clintons, McCain and Palin, and the race of a lifetime - Heilemann, John, 1966-; Halperin, Mark. (New York : Harper, 2010)
From two of the best political reporters in the country comes the gripping inside story of the historic 2008 presidential election.
Her time -- The alternative -- The ground beneath her feat -- Getting to yes -- The inevitables -- Barack in a box -- "They loooooove me!" -- The turning point -- The fun part -- Two for the price of one -- Fear and loathing in the lizard's thicket -- Pulling away and falling apart -- Obama agonistes -- The bitter end game -- The Maverick and his meltdown -- Running unopposed -- Slipping nooses, slaying demons -- Paris and Berlin -- The Mile-High Club -- Sarahcuda -- September Surprise -- Seconds in command -- The finish line -- Together at last.
Includes index.
Keywords: Obama, Barack; Clinton, Hillary Rodham; McCain, John, -- 1936-; Palin, Sarah, -- 1964-; Presidents -- United States -- Election -- 2008.; Political campaigns -- United States -- History -- 21st century..; Elections -- United States -- History -- 21st century; United States -- Politics and government -- 2001-2009.